Comparison of physiological parameters during on-water and ergometer kayaking and their relationship to performance in sprint kayak competitions - Matzka, M.; Zinner, C.; Kunz, P.; Holmberg, H. C.; Sperlich, B. (International Journal of Sports Physiology and Performance, 2021)
Purpose: (1) To compare various physiological indicators of performance during a 5 × 1500-m incremental kayak test performed on an ergometer and on-water and (2) to analyze the relationships between these indicators and the actual competition performance of elite sprint kayakers, aiming to provide information to coaches for evaluating and planning training on-water.